Prevalence and associated factors with syphilis in pregnant women attended in primary health care in a city in the Southeast, Brazil - Maria Esméria Neta; Carla Silvana de Oliveira e Silva; Rene Ferreira da Silva Junior; Tatiane Palmeira Eleutério; Ana Paula Ferreira Holzmann; Edna de Freitas Gomes Ruas; Luciano Oliveira Marques (Revista Brasileira de Saúde Materno Infantil)
Abstract Objectives: to evaluate the prevalence and associated factors with acquired syphilis in pregnant women attended at the primary health care in Montes Claros-MG. Methods: a cross-sectional study carried out with pregnant women enrolled in the Estratégia Saúde da Família (Family Health Strategy) teams in Montes Claros, Minas Gerais, Brazil (2018-2019). Sociodemographic, behavioral and obstetric factors were collected through a questionnaire applied by interview. The result of the Venereal Disease Research Laboratory (VDRL) examination was evaluated. Binary logistic regression analysis was used to determine associated factors with syphilis in pregnancy. Results: the prevalence of syphilis found was 1.7% (CI95%= 1.44–1.96). Pregnant women who graduated from high school had 75% (OR = 0.25; CI95%= 0.08–0.81) less chance of having syphilis, when compared to pregnant women with elementary school. Pregnant women who used illicit drugs during pregnancy (OR = 3.47; CI95%= 1.02–11.82) and consumed alcoholic beverages during pregnancy (OR = 16.35; CI95%= 3. 81–70.20) were more likely to have the disease. Conclusion: schooling, consumption of alcohol and illicit drugs are associated with the diagnosis of syphilis in pregnant women. Therefore, educational programs and interventions are needed to address issues related to prevention, diagnosis, treatment and their risk factors, especially social determinants, and women’s reproductive health issues.